Development of PHBV electrospun fibers containing a borate bioactive glass doped with Co, Cu, and Zn for wound dressings - dos Santos, Verônica Ribeiro; Campos, Tiago Moreira Bastos; Anselmi, Caroline [UNESP]; de Souza, Joyce Rodrigues [UNESP]; Lemes, Ana Paula; Thim, Gilmar Patrocínio; Bottino, Marco Cicero; Borges, Alexandre Luiz Souto [UNESP]; de Sousa Trichês, Eliandra (Wiley, 2024)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanofibers embedded with borate glasses of 45B5 composition doped with Co2+, Cu2+, and Zn2+(46.1 B─O3-26.9-X CaO-24.4 Na─O-2.6 P─Os, X CoO/CuO/ZnO mol % (X = 0–5)) were produced by electrospinning for wound healing applications. Prior to their addition, the glasses exhibited two broad halos typical of a vitreous borate network, which were mainly composed of ring-type metaborate structural units. The particle distribution in the PHBV nanofibers embedded with 45B5 borate bioactive glasses is present in isolated and agglomerated states, being partially coated by a polymeric layer—except for the cobalt-doped glass, which resulted in a successful encapsulation with 100% embedding efficiency. The incorporation of the glasses reduced the PHBV crystallinity degree and its decomposition temperature, as well as its mechanical properties, including Young's modulus, tensile strength, and elongation at break. The neat PHBV fibers and those containing the cobalt-doped glasses demonstrated great cytocompatibility with human keratinocytes (HaCat), as suggested by the high cell viability after 7 days of exposure. Further studies are needed to fully understand the wound healing potential of these fibers, but our results significantly contribute to the area.
Keywords: borate bioactive glass; cytocompatibility; electrospinning; nanofiber; PHBV; wound dressing